The Salic Law: the Forging of a National Myth - Miguel Ángel Maeda (Medievalia)
It is a purpose of the article to analyze the origin and evolution of the Males Law, known incorrectly as Salic Law. This law was an important succession principle of the French monarchy that appeared during the Middle Age and continued existing during the Modernity. The goal of the article is to identify the reasons why the term Salic Law is used wrongly. Furthermore, it is studied the transcendence and importance of that successional principle to the birth of the French national state.